Available markers in the diagnosis and prognosis of kidney cancer - Klaudia Daria Szumna; Dominika Katarzyna Madras; Faustyna Piędel; Patryk Piotr Jasielski; Agata Agnieszka Rocka (Kazimierz Wielki University, 2020)
Introduction and purpose: Renal cell carcinoma (RCC) is the most common kidney cancer that has no symptoms for a long time. It is most often diagnosed accidentally during abdominal ultrasound or abdominal computed tomography, performed primarily due to non-specific clinical symptoms. Despite progress in treatment, late detection is associated with poor prognosis. The aim of the study is to analyze literature (database PubMed) for potential prognostic markers and those used in RCC diagnostics. A brief description of the state of knowledge:  The most common RCC subtype is clear cell renal cell carcinoma(ccRCC). Metastatic ccRCC is associated with poor prognosis. The pathogenesis of ccRCC includes, among others, disorders of miRNA change. These molecules are described as a promising marker of both diagnostic and prognostic. Detection of CD163 + antigen on cancer cells may be useful in assessing the clinical course of ccRCC patients. In clinical diagnosis of RCC, the presence of mutations and epigenetic inactivation of the von Hippel-Lindau (VHL) gene, vascular endothelial growth factor (VEGF) and carbonic anhydrase IX (CIAX) genes are particularly important. Plasma CIAX levels are described as not only a diagnostic and prognostic marker, but also lymph node involvement. There are studies on molecular markers that can also be a therapeutic target, including Caveolin-1 (CAV1), CCL5. Recent research results show a link between PDL1 expression and high-grade tumors. PDL-1 may also be an important prognostic factor. Conclusions: Research on molecular markers is a promising personalized diagnostic and prognostic route. The limitation is the nonspecificity of molecular markers, so research on new and current markers is needed.